1999
DOI: 10.2337/diacare.22.8.1278
|View full text |Cite
|
Sign up to set email alerts
|

Association between stress and glycemic control in adults with type 1 (insulin-dependent) diabetes.

Abstract: The study has shown that recent severe stressors are associated with poorer glycemic control. Positive life events were associated with fair or improved glycemic control. This study has its limitations, and future studies should be prospective in design. While it is not always possible to avoid stress, learning to recognize and cope with stressors may help individuals with diabetes maintain good glycemic control and improve overall quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(66 citation statements)
references
References 1 publication
2
62
0
2
Order By: Relevance
“…However, it is important keep in mind that the differences in life events between diabetic patients and control subjects in the current study could be caused by events of independent illness or manifestations of early stages of diabetes. The institution of insulin treatment leading to improvement of glycemic control after the diagnosis may have induced an independent lifestyle in the diabetic patients (19,20), retrospectively explaining the differences found in social behavior between our diabetic patients and control subjects. Moreover, in keeping with our findings, major life stress and psychiatric disorders are not always found before the onset of childhood diabetes (21).…”
Section: Life Eventsmentioning
confidence: 85%
“…However, it is important keep in mind that the differences in life events between diabetic patients and control subjects in the current study could be caused by events of independent illness or manifestations of early stages of diabetes. The institution of insulin treatment leading to improvement of glycemic control after the diagnosis may have induced an independent lifestyle in the diabetic patients (19,20), retrospectively explaining the differences found in social behavior between our diabetic patients and control subjects. Moreover, in keeping with our findings, major life stress and psychiatric disorders are not always found before the onset of childhood diabetes (21).…”
Section: Life Eventsmentioning
confidence: 85%
“…Stress negatively affects either people with diabetes [24,29,35,36] or without [17][18][19][20][21][22]. Positive life events were associated with improved glycemic control; on the other hand, recent severe stressors were associated with poorer glycemic control [35].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas some research has demonstrated that life challenges are associated with higher levels of urinary epinephrine or norepinephrine (22,24), others found no such relationship (21,25). Other evidence suggests that life challenges may contribute to higher levels of interleukin-6 (IL-6) (26,27), dehydroepiandrosterone sulfate (DHEAS) (28), blood pressure (29 -31), cholesterol (32)(33)(34), triglycerides (31), and glycosylated hemoglobin (35)(36)(37).…”
Section: Link Between Stressful Life Events and Physiologymentioning
confidence: 99%